KONSEP PENDIDIKAN AGAMA ISLAM MENURUT PERSPEKTIF HADIST - Nofri Yandi; Asnibar; Juliana Batu Bara (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Various kinds of concepts of Islamic religious education today in educationalinstitutions both formal and non-formal. So that various kinds of educationalproblems are faced by the community as consumers of educational products.Starting from personal, household, community problems to nation and state.However, there is a concept of education that was born from the perspective of theHadith of the Holy Prophetsa. Namely the basic concepts of education,educational law, objectives, educational institutions, educators, learners,educational materials, methods, adap-adap of education and evaluation of theimplementation of education. So as to give birth to a quality and quality educationprocess and autput as expected. Based on this, the author titled the study of thisarticle, namely the Concept of Islamic Education According to the HadithPerspective. With the aim is to be directed where we want to take the students ofthis nation in the future. The method that the author lived in the study in this studyis a literature review and compares various kinds of literacy, articles, figures andscholars so that we can conclude that the concept of Islamic religious education isbased on the Qur'an, the Sunnah of the Prophet SAW, ijtihad of scholars, peoplewho have succeeded in giving examples so that the implementation is full ofsincerity and sincerity which in the end becomes a reflection of example incontinuing personal life, family, community of nation and state.